2011
DOI: 10.4049/jimmunol.1100299
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2 Regulates CD4+ Memory T Cell Trafficking across Blood Vascular Endothelium and Primes These Cells for Clearance across Lymphatic Endothelium

Abstract: Memory lymphocytes support inflammatory and immune responses. To do this, they enter tissue via blood vascular endothelial cells (BVEC) and leave tissue via lymphatic vascular endothelial cells (LVEC). In this study, we describe a hierarchy of signals, including novel regulatory steps, which direct the sequential migration of human T cells across the blood and the lymphatic EC. Cytokine-stimulated (TNF and IFN) human BVEC preferentially recruited memory T cells from purified PBL. Lymphocyte recruitment from fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
(39 reference statements)
2
27
0
Order By: Relevance
“…Confluent cultures were treated for 24h with patient or control plasma EV mixed 1:1 with culture medium including 5U/ml heparin to maintain anticoagulation, with 0 or 5 U/ml tumour necrosis factor-α (TNF) added for the last 4h. A flow-based adhesion assay was performed as described previously [36]. Briefly, ibidi slides were mounted on the stage of a phase-contrast video microscope enclosed in a 37°C perspex chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Confluent cultures were treated for 24h with patient or control plasma EV mixed 1:1 with culture medium including 5U/ml heparin to maintain anticoagulation, with 0 or 5 U/ml tumour necrosis factor-α (TNF) added for the last 4h. A flow-based adhesion assay was performed as described previously [36]. Briefly, ibidi slides were mounted on the stage of a phase-contrast video microscope enclosed in a 37°C perspex chamber.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that fibroblasts may retain transmigrated T-cells, either because transendothelial migration altered the T-cells or because the fibroblast monolayers became less easy to penetrate when cultured with EC. Notably, our previous studies showed that after migration through EC, T-cells passed more efficiently through monolayers of lymphatic endothelial cells (Ahmed et al, 2011), indicating that their migratory ability is not impaired. Others have reported that dermal fibroblasts isolated from patients with scleroderma promoted mononuclear leukocyte migration through EC cultured on filters (Denton et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Signals from chemokines (which may vary depending on the inflammatory stimulus) activate the integrins to stabilise the initial interactions (e.g. McGettrick et al, 2009b; Piali et al, 1998), while a downstream signal from prostaglandin D 2 promotes efficient transendothelial migration (Ahmed et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…PGD 2 binding to this receptor is also very important for CD4+ T cell trafficking and motility (116, 117). When produced at high concentrations by mast cells, as seen in allergic inflammation, there is a consequent activation and recruitment of Th2 cells toward the PGD 2 producing sites (118, 119).…”
Section: Eicosanoids and Related Mediators In T Cell Function/biologymentioning
confidence: 99%